Digitalization and the green transition: Different challenges, same policy responses? - Marius R. Busemeyer; Sophia Stutzmann; Tobias Tober (Regulation & Governance, 2024)
How do citizens perceive labor market risks related to digitalization and the green transition, and how do these risk perceptions translate into preferences for social policies? We address these questions in this paper by studying the policy preferences of individual workers on how governments should deal with the two labor market challenges of digitalization and the green transition. Employing novel cross-country comparative survey data including a vignette experiment for six advanced postindustrial economies, we probe to what extent the different labor market challenges are associated with differences in preferences, distinguishing between support for social investment policies on the one hand and compensatory policies on the other. A first finding is that even though individuals perceive different levels of labor market risk due to the green transition and digitalization, their preferences for social policy responses do not differ systematically across the two risks. Instead, we find that social policy preferences are affected by individual-level and, to some extent, country-level contextual factors. Confirming previous work, higher perceived labor market risk is associated with more support for compensatory policies but less support for social investment.
Keywords: 330; digitalization; green transition; knowledge economy; OECD countries; public opinion; public policy